Arabidopsis CK2 family gene CKB3 involved in abscisic acid signaling - Yuan,C. (2021)
Abstract CKB3 is a regulatory (beta) subunit of CK2. In this study Arabidopsis thaliana homozygous T-DNA mutant ckb3 was studied to understand the role of CKB3 in abscisic acid (ABA) signaling. The results shown: CKB3 was expressed in all organs and the highest expression in the seeds, followed by the root. During seed germination and root growth the ckb3 mutant showed reduced sensitivity to ABA. The ckb3 mutant had more stomatal opening and increased proline accumulation and leaf water loss. The expression levels of number of genes in the ABA regulatory network had changed. This study demonstrates that CKB3 is an ABA signaling-related gene and may play a positive role in ABA signaling.